The relationship between health literacy and health-related quality of life in Chinese older adults: a cross-sectional study - Li, Hui; Tao, Simin; Sun, Silu; Xiao, Ying; Liu, Yongbing (Frontiers in Public Health, 2024)
Background This study aimed to examine the relationship between health literacy and health-related quality of life in older adults. Methods A cross-sectional survey design was used. We used a self-administered questionnaire to assess sociodemographic factors of older adults, the Chinese Citizen Health Literacy Questionnaire (HLQC) and the 36-item Chinese version of the Short Form 36 (SF-36) to measure health literacy and quality of life, respectively, among older adults. Between September 2011 and June 2012, information was collected from 1,396 older adults in 44 nursing homes in four cities through face-to-face interviews. Results The mean health literacy level of older adults in nursing homes was relatively low (71.74 ± 28.35). Health-related quality of life scores were moderate (104.77 ± 16.92). There were statistically significant differences in the effects of health literacy, education level, former occupation (professional), marital status (widowed) and race on health-related quality of life. Conclusion Improving health literacy is considered an important intervention to promote health-related quality of life in older adults in nursing homes.